As condições de Serre e o critério Jacobiano - Lima, Johnny Albert dos Santos (2018)
In this work we will present two important tools of the Commutative Algebra: the Serre’s conditions and the Jacobian criterion. Later, we will explore applications that aim to characterize normal rings and present an effective calculation to obtain the symbolic powers of an ideal via Jacobian matrices.